Sequelae of fetal growth restriction - Ismail, Hamizah; Yao-Lung, Chang (Excerpta Medica Asia Ltd., 2012)
Intrauterine growth restriction (IUGR) is a unique and important issue for obstetricians. The acute neonatal consequences of IUGR are perinatal asphyxia and neonatal adaptive problems. However, the long-term outcomes of such neonates are less discussed because obstetricians usually only care for pregnant woman until delivery. The aim of this article is to review the sequelae, especially the long-term effects including the neurological, cardiovascular, renal, and metabolic effects of the growth restriction in an obstetrician's view.